Molecular Detection of Enterobacteriaceae and Escherichia coli from Water - Hilson, Eunike Ilona; Prana, Mertha; Satwika, Dhira (Proceeding International Conference on Global Resource Conservation, 2015)
Well water has become the important source for public daily activities, especially as drinking water. Enterobacteriaceae is a bacterial group, often found in well water. There are 8 genus of Enterobacteriaceae consider as enteric group because of its relationship to fecal bacteria from human and animal gastrointestine.Â Escherichia coli, a member of this group, is one of the best microbiological fecal indicator that have been used for water monitoring. The presence of this bacterial group is of human interest, especially related to their pathogenic characteristic and as the fecal indicator for water quality. This is the objective of this research to evaluate the specivity of new primers which were deduced from partial sequences of rpoB, gyrB and lacZ genes specifically designed for Enterobacteriaceae and E. coli detection. After being optimized by mean of setting the annealing temperature, they are used for in vitro analysis. The result showed the primers are specific enough for Enterobacteriaceae and E. coli detection.Keywords: Â Enterobacteriaceae, E. coli, gyrB, lacZ, rpoB